The main features of military law in Ukrainian lands during the XVIII century - B. H. Holovko (Bulletin of Kharkiv National University of Internal Affairs)
The study of Ukrainian military history in general and military law in particular is of paramount importance in the context of Russian aggression against Ukraine. The period of the 18th century occupies a prominent place in Ukrainian history due to the incorporation of Ukrainian lands into other states, primarily the Russian Empire. Codification by the Russian administration was understood as the absorption of Ukrainian law into Russian law and the complete obliteration of the Ukrainian legal tradition. However, Ukrainian codifiers, using the principle of legal continuity, were able to create original legal collections which had an obvious connection with previous achievements in the field of law. It has been established that the focus of regulation of military-legal relations was on the problems of mobilisation, which was applicable to all segments of Ukrainian society. It has been determined that military service has become the main condition for acquiring land ownership. The article enshrines in law the need to abolish the possibility of evading mobilisation by transferring land as a loan, pledge, inheritance, etc. The law required military service by the legal owner of the land. It has been found that the law provided for the possibility of refusing conscription in case of emergency, but even in such circumstances, the landowner had to take care and appoint another serviceman from among his relatives. Moreover, it has been proved that legal norms also regulated the prosecution of military personnel who violated law and order during redeployment, cantonment, and communication with each other and the local population. In addition, it has been shown that the most common universal type of punishment for violation of military laws was a fine, but certain features of the punishment were determined by the social status of the offender – the nobility was deprived of their social privileges as an additional punishment, and lower-ranking soldiers were subject to corporal punishment. Thus, it has been determined that military legal norms paid special attention to the regulation of personnel policy: people who were unconditionally brave, experts in military affairs, and those who enjoyed universal respect were recommended for command positions. Considering all the above circumstances can be useful in developing a new military doctrine of Ukraine and enrich it with invaluable historical experience.